Mononuclear inflammatory infiltrate and microcirculation injury in acute rejection: Role in renal allograft survival - Dos Santos, Daniela Cristina [UNESP]; Andrade, Luís Gustavo Modelli de [UNESP]; De Carvalho, Maria Fernanda Cordeiro [UNESP]; Neto, Francisco Alves Moraes; Viero, Rosa Marlene [UNESP] (Taylor & Francis, 2013)
This study aimed at investigating associations between monocytes/ macrophages (Mo) infiltration and three important criteria associated with acute antibody-mediated rejection: C4d staining, microcirculation injury, and graft survival time. By quantitative analysis, Mo were counted in peritubular capillaries and in the interstitial compartment (peritubular/interstitial Mo), and they were also identified in glomeruli (glomerular Mo). The study included 47 patients who received renal allograft between 1991 and 2009. Capillaritis and glomerulitis were classified by the Banff scoring system, and C4d and Mo were analyzed by immunohistochemistry. In the quantitative analysis, the mean values of 50 Mo per 10 high-power fields (HPF) and 4 Mo per glomerulus were used as cut-off points for the peritubular/interstitial and glomerular compartments, respectively. Positive C4d cases were associated with the groups of biopsies with a mean value ≥50 Mo per 10 HPF (p = 0.01) and ≥4 Mo per glomerulus (p = 0.02). The group with a mean value ≥4 Mo per glomerulus also showed association with the presence of glomerulitis (p = 0.02). Peritubular/ interstitial Mo did not associate with glomerulitis. Capillaritis did not show association with peritubular/interstitial or glomerular Mo. As regards graft survival, the infiltration of Mo in glomeruli interfered with allograft survival (p = 0.01). The group with a mean value of ≥4 glomerular Mo presented worse survival at the time of the 1-year follow-up. According to the literature, our data showed that infiltration of mononuclear cells was associated with C4d staining, microcirculation injury, and glomerulitis, in particular, and that glomerular macrophages could influence renal allograft survival. Copyright © 2013 Informa Healthcare USA, Inc.
Keywords: Acute rejection; C4d; Glomerulitis; Graft survival; Microcirculation; Monocytes/Macrophages; Renal transplantation; complement component C4d; acute graft rejection; adult; capillaritis; clinical article; controlled study; disease association; female; follow up; glomerulitis; glomerulus capillary; graft survival; human; human cell; human tissue; immunohistochemistry; inflammatory infiltrate; kidney allograft rejection; macrophage; male; microcirculation; monocyte; mononuclear cell; priority journal; quantitative analysis; retrospective study; scoring system; survival time